Improvement of the Orthopedic Method in Complex Treatment in Patients with Periodontal Diseases - Chakkanov Fahritdin Khusanovich (Academia One Publishing, 2023)
The aim of the work is to increase the effectiveness of orthopedic treatment of patients with periodontal diseases.
Keywords: Orthopedic Treatment; Periodontal Diseases